Does spatial location matter? Traditional therapy utilisation among the general population in a Ghanaian rural and urban setting. Issue 3 (June 2015) - Gyasi, Razak Mohammed; Asante, Felix; Segbefia, Alexander Yao; Abass, Kabila; Mensah, Charlotte Monica; Siaw, Lawrencia Pokuah; Eshun, Gabriel; Adjei, Prince Osei-Wusu
Graphical abstract